Prevalence of Sexual Dysfunction among Expectant Women - Michelly Nóbrega Monteiro; Eudes Euler de Souza Lucena; Patricia Uchoa Cabral; José Queiroz Filho; Janice Queiroz; Ana Katherine Gonçalves (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Purpose To identify pregnancy as a causative factor of sexual dysfunction among expectant women. Methods A prospective study with 225 expectant mothers seen in the prenatal clinic of a federal university. Sexual function was evaluated by means of the Female Sexual Function Index (FSFI), and all domains were analyzed (desire, arousal, lubrication, orgasm, satisfaction, and pain). Initially, a univariate analysis of the sample was done. The averages for each domain according to the risk of sexual dysfunction (FSFI ≤ 26.5) were compared using the Student's t-test for independent samples. The strength of the correlation between sexual dysfunction and all sociodemographic, clinical and behavioral variables was measured by the Chi-Square (X2) test. Then, odds ratios (ORs) and their confidence intervals were assigned to perform a bivariate analysis. Any p values less than 0.05 were considered significant. Results Approximately two-thirds of the women (66.7%) showed signs of risk of sexual dysfunction (FSFI ≤ 26.5). Within these cases, all sexual dysfunction domains (desire, arousal, lubrication, orgasm, satisfaction, and pain) were found to be statistically significant (p < 0.001). The domains most affected were desire (2.67), satisfaction (2.71) and arousal (2.78). Conclusions Pregnancy appears to be an important causative factor of sexual dysfunction among pregnant women.